(untitled) (International Seven Journal of Multidisciplinary, 2024)
In the past decade, environmental issues have gained significant prominence in public discourse, leading to increased awareness and more favorable attitudes toward ecological concerns. This shift has been reflected in the growing active participation of individuals and communities in addressing environmental challenges, highlighting the critical importance of sustainability and the urgent need to tackle these issues. As sustainability gains global prominence, consumer purchasing behaviors are also evolving. Consumers are now more attentive to companies’ sustainable practices when selecting products or services, driven by a deeper understanding of the environmental and social impacts of their consumption choices. However, effectively communicating sustainability presents a significant challenge. It involves more than merely promoting green initiatives; it requires building trust and authenticity amidst a landscape of expectations and public scrutiny. The rising prevalence of greenwashing, where companies exaggerate or distort their environmental actions, threatens consumer and investor confidence in eco-friendly products. To address this issue, it is crucial for companies to adopt a transparent approach, supported by verifiable data and independent certifications, and to set clear and measurable goals. The study by Oliveira Jr (2015) reveals that consumer purchase intentions are positively influenced when they are informed about companies’ sustainable actions, supporting the findings of Choi and Ng (2011). Initiatives that reduce pollution, use recyclable packaging, and promote resource conservation have a positive impact on purchase intention. However, the communication of social initiatives, such as adherence to ethical principles and laws, did not show a significant effect.